Positive effects of organic farming on below-ground mutualists: large-scale comparison of mycorrhizal fungal communities in agricultural soils - Verbruggen, Erik; Röling, Wilfred F. M.; Gamper, Hannes A.; Kowalchuk, George A.; Verhoef, Herman A.; van der Heijden, Marcel G. A. (The New phytologist, 2010)
The impact of various agricultural practices on soil biodiversity and, in particular, on arbuscular mycorrhizal fungi (AMF), is still poorly understood, although AMF can provide benefit to plants and ecosystems. Here, we tested whether organic farming enhances AMF diversity and whether AMF communities from organically managed fields are more similar to those of species-rich grasslands or conventionally managed fields. To address this issue, the AMF community composition was assessed in 26 arable fields (13 pairs of organically and conventionally managed fields) and five semi-natural grasslands, all on sandy soil. Terminal restriction fragment length polymorphism community fingerprinting was used to characterize AMF community composition. The average number of AMF taxa was highest in grasslands (8.8), intermediate in organically managed fields (6.4) and significantly lower in conventionally managed fields (3.9). Moreover, AMF richness increased significantly with the time since conversion to organic agriculture. AMF communities of organically managed fields were also more similar to those of natural grasslands when compared with those under conventional management, and were less uniform than their conventional counterparts, as expressed by higher β-diversity (between-site diversity). We suggest that organic management in agro-ecosystems contributes to the restoration and maintenance of these important below-ground mutualists.